Trop2 enhances invasion of thyroid cancer by inducing MMP2 through ERK and JNK pathways - Guan, Hongyu; Guo, Zejun; Liang, Weiwei; Li, Hai; Wei, Guohong; Xu, Lijuan; Xiao, Haipeng; Li, Yanbing (BMC cancer, 2017)
Mounting evidence has showed that Tumor-associated calcium signal transducer 2 (Trop2) is upregulated in various kinds of human cancers and plays important roles in tumorigenesis. However, the expression status and functional significance of Trop2 in thyroid cancer are largely unknown. We first determined the expression of Trop2 by using RNAseqV2 data sets for thyroid cancer deposited on The Cancer Genome Atlas (TCGA) website. The expression of Trop2 was then confirmed by real-time reverse transcription-polymerase chain reaction (RT-PCR) and immunohistochemistry assays. Cell invasion and migration were assessed by conducting Transwell and wound healing assays. Furthermore, we explored the underlying mechanisms by using real-time RT-PCR, Western blot, zymography, and luciferase reporter assays. In this study, we demonstrated that the expression of Trop2 was significantly elevated in thyroid cancer and that its expression level was correlated with the tumor-node-metastasis (TNM) staging and N classification. Dysregulation of Trop2 altered the invasive capability of thyroid cancer cells. Further mechanistic study revealed that MMP2 expression was upregulated by Trop2. Moreover, we found that the effects of Trop2 were dependent on ERK and JNK pathways. The results from clinical specimens showed that Trop2 expression correlated with MMP2 expression in primary thyroid cancer. The current study suggests that elevated expression of Trop2 may represent an important molecular hallmark that is biologically and clinically relevant to the progression of thyroid cancer.